Literature Study on the Utilization of Interactive Multimedia in Learning for Early Child Students - Nurhayati, Fety Rosyida; Sudiyanto, Sudiyanto; Djono, Djono (Universitas Sebelas Maret, 2023)
In recent years, there has been an increasing interest in exploring the potential of interactive multimedia as a learning tool for early child students, as it offers various engaging and interactive elements that can enhance their learning experiences and outcomes. This study aims to provide an explanation regarding the application of interactive multimedia in learning. This research was carried out using the Literature Review method. The data sources which later became the subject of this study consisted of 13 selected articles based on a review of keywords and the year of publication of relevant scientific articles and books. The data analysis technique in this research uses descriptive analysis techniques, so that the findings of the articles can be analyzed descriptively in their application to learning activities. The results of a review of several literatures show that applications and multimedia content can be used as learning resources during learning, and ensure that the learning process remains active, dynamic and efficient. It is known that through the application of interactive multimedia it is also possible to increase the interest and learning motivation of early childhood students. So, it is hoped that this interactive multimedia can certainly be adopted by teachers during learning activities.